Developments in effective use of volatile organic compound analysis to assess flavour formation during cheese ripening - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2021)
In the burgeoning demand for optimization of cheese production, ascertaining cheese flavour formation during the cheese making process has been the focal point of determining cheese quality. In this research reflection, we have highlighted how valuable volatile organic compound (VOC) analysis has been in assessing contingent cheese flavour compounds arising from non-starter lactic acid bacteria (NSLAB) along with starter lactic acid bacteria (SLAB), and whether VOC analysis associated with other high-throughput data might help provide a better understanding the cheese flavour formation during cheese process. It is widely known that there is a keen interest to merge all omics data to find specific biomarkers and/or to assess aroma formation of cheese. Towards that end, results of VOC analysis have provided valuable insights into the cheese flavour profile. In this review, we are pinpointing the effective use of flavour compound analysis to perceive flavour-forming ability of microbial strains that are convenient for dairy production, intertwining microbiome and metabolome to unveil potential biomarkers that occur during cheese ripening. In doing so, we summarised the functionality and integration of aromatic compound analysis in cheese making and gave reflections on reconsidering what the role of flavour-based analysis might have in the future.
Keywords: Biomarkers; Cheese; flavour; ripening; VOC analysis; LACTIC-ACID BACTERIA; WHITE-BRINED CHEESE; LACTOCOCCUS-LACTIS; ADJUNCT CULTURES; AROMA FORMATION; LACTOBACILLUS; GROWTH; STARTER; PHYSIOLOGY; STRAINS